The Effect of the Functional Approach on the Expressive Performance of Fifth-Grade Literary Students (Journal of the College of Basic Education, 2025)
The research aimed to identify the effect of the functional approach on the expressive performance of fifth-grade literary students. The research sample consisted of (66) students, divided into two groups: an experimental group and a control group, each containing (33) students. After conducting statistical equivalence between the two research groups on a number of statistical variables, determining the scientific material, and adopting appropriate correction criteria, the method of sequential post-tests was followed. After extracting the averages of the students in both groups and using the t-test for two independent samples, it was found that the students in the experimental group outperformed the students in the control group. This indicates that the functional approach has an impact on expressive performance. In light of this, the researchers made a number of recommendations and proposals.